2015
DOI: 10.1002/pca.2584
|View full text |Cite
|
Sign up to set email alerts
|

Use of time‐resolved spectroscopy as a method to monitor carotenoids present in tomato extract obtained using ultrasound treatment

Abstract: Extracted lycopene appeared unaffected by ultrasound treatment, while other constituents (chlorophyll and phytofluene) were degraded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Indeed this was confirmed in a recent study of lycopene, a carotenoid commonly found in tomatoes, other red fruit and some vegetables [24]. Commercially available lycopene (LYC) was compared with a control lycopene sample extracted from tomato and lycopene extracted from tomato following ultrasonic treatment at 584 kHz for 15 min (T15) and 60 min (T60) [25]. Fig.…”
Section: Dd-375l (378nm) Fluorocube Ultrafastmentioning
confidence: 55%
See 1 more Smart Citation
“…Indeed this was confirmed in a recent study of lycopene, a carotenoid commonly found in tomatoes, other red fruit and some vegetables [24]. Commercially available lycopene (LYC) was compared with a control lycopene sample extracted from tomato and lycopene extracted from tomato following ultrasonic treatment at 584 kHz for 15 min (T15) and 60 min (T60) [25]. Fig.…”
Section: Dd-375l (378nm) Fluorocube Ultrafastmentioning
confidence: 55%
“…shows the results of decay analysis for the 4 lycopene samples according to Results of the 3-exponential fluorescence decay analysis of the 4 lycopene samples according to Eq.6 and including average decay time <>[25]. Details are provided in the caption toFig 12.…”
mentioning
confidence: 99%
“…However, it is difficult to observe any emission related to lycopene. Instead, there are emissions close to 500 nm (with shorter wavelength excitation) and 670 nm, The shorter wavelength emission is consistent with the presence of phytofluene, with the excitation coinciding with the absorption peaks [ 48 ] and there are reports of its emission at this wavelength, although this can be affected by both solvent and temperature [ 74 , 79 ]. The longer wavelength emission can be assigned to the presence of cholorphyll [ 43 , 57 , 60 ].…”
Section: Resultsmentioning
confidence: 88%
“…Relatively low ultrasound frequencies (24 kHz) appear benign to carotenoids [ 68 ], including lycopene [ 69 ]. Here, we will make use of a higher frequency of 583 kHz [ 48 ]. The biosynthetic pathway involved in producing lycopene contains many intermediates, generally considered starting with geranylgeranyl pyrophosphate and proceeding to lycopene, which can be further involved in the formation of cyclic carotenoids [ 5 , 70 , 71 , 72 , 73 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation